Secular trend of body dimensions in highly qualified wrestlers - Godina, E.; Sirazetdinov, R. E.; Negasheva, M. A. (Collegium Antropologicum, 2022)
The purpose of the paper was to study the physique of highly qualified martial art athletes engaged in different types of wrestling, and to perform a retrospective analysis of the morphological characteristics of wrestlers examined since the early 1920s. The materials of the anthropometric survey of 48 athletes engaged in different types of wrestling with qualification from the candidate for master of sports and above were used for this purpose and compared to the "control group" of young men (N = 97) who were not engaged in sports (similar to the group of athletes by age, ethnicity and percentage of individuals with different weight categories). A set of morphological traits was established that contributed to the successful achievements in sports. When comparing the physique of modern athletes with that of the wrestlers surveyed in the early and mid-20th century (the 1920s and 1960s), it has been shown that the secular trend towards increase in height typical for modern population, was expressed in athletes to a much lesser extent. Striking similarities were revealed for absolute and relative dimensions characterizing the skeletal body proportions of the wrestlers, which pointed to the secular stability of this sports morphotype. The obtained results can be used as additional morphological criteria for sports selection, professional orientation and prediction of competitive success.